Green infrastructure development opportunities in rural settlements - Valánszki , István; Virág, Debóra; Kiszter , István Balázs; Boromisza, Zsombor (4D Journal of Landscape Architecture and Garden Art, 2021)
The term of green infrastructure (GI) became widespread all over the world especially in relation to settlement planning. Because of the complexity and multifunctionality of the concept it can be applied in regional and rural development as well. The European Union intends to integrate the concept of green infrastructure into several policy fields, strategies. In Hungary during the last years, many important GI related strategies have been elaborated. However, the already existing complex projects and case studies mainly focusing on cities or bigger towns, settlements. In our study, we would like to give an example of a complex GI planning and development in a case of a smaller settlement on the Hungarian countryside. Following the local government’s and stakeholders’ needs our goal was to give a practice-oriented proposal for GI development for the settlement implementing many suggestions from the formerly mentioned research reports and handbooks. We dealt with a typical rural settlement, called Kisszállás from the Great Hungarian Plain as case study. Our analyses focused on GI of the unbuilt and built-up areas of the settlement as well as the border zones between these two parts of the settlement. Our results showed many shortcomings related to the GI, however, we found also several untapped potentials. Based on these results, we developed the GI concept of Kisszállás. We targeted two main directions: 1, the professional maintenance, protection of existing GI system; 2, elaboration of conceptual development ideas focusing on two target areas. With these targets a significant improvement can be achieved in the green areas of the settlement. Our practice-oriented proposal-package represents an example how it is possible to implement the international and national policies, recommendations into local actions.